2012
DOI: 10.1063/1.4770308
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline silicon interface passivation improvement with a-Si1−xCx:H and its application in hetero-junction solar cells with intrinsic layer

Abstract: Excellent passivation of an n-type Czochralski crystalline silicon surface is made possible by the deposition of hydrogenated silicon carbide (Si1−xCx:H) layers in the electron cyclotron resonance chemical vapor deposition. We investigate the structural effect with various CH4/SiH4 dilution ratios, and the lowest effective surface recombination velocity (21.03 cm/s) that can be obtained. We also demonstrate that the Voc can be improved more than 200 mV by inserting Si1−xCx:H layers to form hetero-junction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The tensile stress in amorphous Ge films is due to the intrinsic stress, and the bombardment effect cause the intrinsic stress becomes compressive as the gas pressure decreases. Thornton et al 24 also reported the similar condition about the intrinsic stress in the thin films. According to these reference paper results, we speculate that the tensile strain in our Ge epilayers at high process pressure is due to intrinsic stress.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The tensile stress in amorphous Ge films is due to the intrinsic stress, and the bombardment effect cause the intrinsic stress becomes compressive as the gas pressure decreases. Thornton et al 24 also reported the similar condition about the intrinsic stress in the thin films. According to these reference paper results, we speculate that the tensile strain in our Ge epilayers at high process pressure is due to intrinsic stress.…”
Section: Resultsmentioning
confidence: 64%
“…In this study, we used ECR-CVD to grow Ge epilayers on n-type <100> CZ silicon wafers with a resistivity of 1-10 -cm z E-mail: 102389003@cc.ncu.edu.tw diced at a low growth temperature of 220 • C. The ECR-CVD process provides a number of advantages for the growth of films, such as high crystallinity, less ion damage to the surface, and high deposition rates. 23,24 During process, we modulate the process pressure and main coil current to control the strain in the Ge epilayers. The main coil current is used to control the plasma position in the ECR chamber.…”
Section: Methodsmentioning
confidence: 99%
“…One of the promising materials for passivation is hydrogenated amorphous silicon carbide (aSi 1-x C x :H) [4][5][6]. This material have several advantages compared to hydrogenated amorphous silicon such as the wide tunable optical bandgap, higher hydrogen content, lower absorption coefficient, and excellent thermal and mechanical stability [4]. However, the negative effects of carbon diffusion are major concerns that could degrade the solar cell performance.…”
Section: Introductionmentioning
confidence: 99%
“…Surface passivation enhances the performance of the cell by saturating the dangling bonds which reduces the recombination losses at the aSi:H/cSi interface [3]. One of the promising materials for passivation is hydrogenated amorphous silicon carbide (aSi 1-x C x :H) [4][5][6]. This material have several advantages compared to hydrogenated amorphous silicon such as the wide tunable optical bandgap, higher hydrogen content, lower absorption coefficient, and excellent thermal and mechanical stability [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenated amorphous silicon (a-Si:H) and related thin films have been implemented in device applications, including absorbers in thin film solar cells, [11][12][13][14][15][16][17][18][19][20][21] passivation layers in wafer silicon photovoltaics, [22][23][24][25][26][27][28] and imaging layers in uncooled infrared (IR) sensing microbolometers. [29][30][31][32][33][34][35][36][37] The a-Si:H network varies in terms of incorporated hydrogen content and bonding configuration, [23,26,[38][39][40][41] the presence of nanoscale voids and vacancy structures, [38,39] and film stress [42] as deduced from experimental measurements.…”
Section: Introductionmentioning
confidence: 99%